2011
DOI: 10.1007/s11250-011-9864-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of melatonin and progestagen–eCG to initiate reproductive activity in prepuberal Awassi ewe lambs

Abstract: This experiment was conducted to evaluate the effect of administering hormonal treatments (melatonin and progestagen/equine chronic gonadotropin (eCG)) on advancing puberty in Awassi ewe lambs. Fifty-one 6-month-old ewe lambs of similar body weights (around 28 kg) were randomly assigned into four treatment groups; control (CON; n = 14), melatonin (MEL; n = 13), melatonin plus progestagen-eCG (MELPP; n = 11), and progestagen-eCG (PP; n = 13). Ewe lambs in the PP and MELPP groups were fitted with intravaginal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Martinez et al (2015) used a combined stimulation method that resulted in 95% ovulation in the ewe lambs. In a study comparing combined treatment with melatonin treatment alone, ovulation was not observed in ewe lambs treated with melatonin alone but was observed in >90% of the animals treated with melatonin + progesterone and melatonin + progesterone + PMSG (Sawalha et al, 2011). Similar stimulation studies discussed above show that repeated sulpiride administration can produce above‐average stimulation in pre‐pubertal ewe lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al (2015) used a combined stimulation method that resulted in 95% ovulation in the ewe lambs. In a study comparing combined treatment with melatonin treatment alone, ovulation was not observed in ewe lambs treated with melatonin alone but was observed in >90% of the animals treated with melatonin + progesterone and melatonin + progesterone + PMSG (Sawalha et al, 2011). Similar stimulation studies discussed above show that repeated sulpiride administration can produce above‐average stimulation in pre‐pubertal ewe lambs.…”
Section: Discussionmentioning
confidence: 99%
“…within 6 days (Bartlett et al, 2009). In ruminants, eCG treatment has been less frequently exploited to stimulate early puberty, however, multiple studies showed that it works successfully in sheep (Sawalha et al, 2011). In dairy cattle, a major reproductive issue is the duration of the postpartum anestrus because of the economic consequences on production.…”
Section: Resultsmentioning
confidence: 99%
“…Gonadotropic supplementation did not enhance reproductive performance of the progesterone-treated females, which indicated that the need for gonadotropin stimulation might diminish with advancement into the breeding season. In contrast, gonadotropic stimulation following progestogen treatment advanced the breeding and lambing season of spring-born ewe lambs exposed to rams during the breeding season at 7 months of age (Stellflug et al, 2001;Sawalha et al, 2011). However, these studies did not include a progestogen-only treatment group which precluded an assessment of the requirement for gonadotropic stimulation beyond the progesterone pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with eCG after progestogen priming also induced fertile estrus and advanced ages at first conception and lambing in spring-born lambs (Stellflug et al, 2001;Sawalha et al, 2011). Those data led to the suggestion that gonadotropic support might improve reproductive performance of nulliparous ewes bred during the breeding season.…”
Section: Introductionmentioning
confidence: 93%